The Influence of Brand Image and Product Innovation on Purchasing Decision of Kopi Kenangan at Tunjungan Plaza Surabaya - Gladys Adella Permatasari (Jurnal Ekonomi, 2021)
The development and growth of the culinary business is currently increasing in Indonesia, especially in Surabaya, especially coffee shops, this is marked by the rise of restaurants, cafes and coffee shops. Kopi Kenangan is one of the shops that popularized a typical Indonesian coffee milk drink which is popular with the name "Es Kopi Kenangan Mantan”. This study aims to analyze whether brand image and product innovation partially influence purchasing decisions of Kopi Kenangan at Tunjungan Plaza Surabaya and whether the brand image and product innovation also simultaneously influences the purchasing decision of Kopi Kenangan at Tunjungan Plaza Surabaya. This research is a quantitative study. Total sample of this study is 104 Consumers of Kopi Kenangan in Tunjungan Plaza. The type of sample used is simple random sample. The researcher uses interviews, questionnaires and observations to obtain data. The results show that partially brand image and product innovation have a significant effect on purchasing decisions. Brand Image and Product Innovation have a simultaneous effect on purchasing decisions for Kopi Kenangan at Tujungan Plaza.